A Systematic Literature Review on Agri-Food Supply Chain Transparency - Ikram Hasan; Md. Mamun Habib; Zulkifflee Mohamed (International Journal of Supply Chain Management, 2023)
The agri-food supply chain (ASC), integral to global sustenance, faces pressing challenges related to transparency and traceability. This systematic literature review (SLR) delves into the transformative potential of emerging digital technologies, namely Blockchain, IoT, and Digital Financial Solutions, in addressing these challenges. Through a rigorous selection process, 88 papers were meticulously reviewed, revealing a growing academic interest in the domain. The review underscores the individual and combined potentials of these technologies in enhancing transparency, fostering trust, and ensuring efficiency in the ASC. The study further highlights the synergistic benefits of integrating these technologies, emphasizing their role in real-time monitoring, secure transactions, and collaborative operations. The findings illuminate a promising future for the ASC, advocating for continued research and innovation in harnessing these technologies to meet the evolving demands of consumers and stakeholders.